2018
DOI: 10.1111/bcpt.12991
|View full text |Cite
|
Sign up to set email alerts
|

β‐2 Agonists as Misusing Drugs? Assessment of both Clenbuterol‐ and Salbutamol‐related European Medicines Agency Pharmacovigilance Database Reports

Abstract: A recent years' increase in misusing levels of image- and performance- enhancing drugs (IPEDs) has been observed. Out of these drugs, beta-2 agonists have recently emerged for their potential of misuse, especially for slimming and bodybuilding purposes. To this perspective, clenbuterol ('the size zero pill') has been reported as being both popular and widely available from the illegal market. All clenbuterol and salbutamol misuse/abuse/dependence/withdrawal/overdose/off-label spontaneous reports (2006-2016) fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 43 publications
2
26
0
1
Order By: Relevance
“…Aside from the reported AAFs of beta 2 ‐agonists each year, there is a widespread abuse of these substances among bodybuilders and recreational strength athletes . Around 20% of anabolic steroid abusers have reported that beta 2 ‐agonists are part of the drugs they use for leanness .…”
Section: Antidoping Regulations Adverse Analytical Findings and Abusmentioning
confidence: 99%
See 1 more Smart Citation
“…Aside from the reported AAFs of beta 2 ‐agonists each year, there is a widespread abuse of these substances among bodybuilders and recreational strength athletes . Around 20% of anabolic steroid abusers have reported that beta 2 ‐agonists are part of the drugs they use for leanness .…”
Section: Antidoping Regulations Adverse Analytical Findings and Abusmentioning
confidence: 99%
“…Accordingly, beta 2 ‐agonist abuse is not only a problem that pertains to elite sport. While there is a high illicit use of clenbuterol among bodybuilders, occurrences of overdosing and off‐label use are actually higher for salbutamol than for clenbuterol in the European Union …”
Section: Antidoping Regulations Adverse Analytical Findings and Abusmentioning
confidence: 99%
“…Our local clinical biochemist suggested theophylline, also a methylxanthine, as a potential cause, having previously seen cases similar to this. The features of acute chest pain, palpitations and vomiting, with hypokalaemia, hypophosphataemia and hyperglycaemia on laboratory testing and the ECG demonstrating sinus tachycardia and ischaemic changes, matched reports of β-agonist toxicity 2 8. However, β-agonist toxicity was considered unlikely, given the absence of comorbidities and daily medications, plus the family denied any β-agonist medications being kept in the household.…”
Section: Differential Diagnosismentioning
confidence: 77%
“…Clenbuterol is an oral β2-agonist with anabolic and lipolytic effects, used off-licence as a ‘fat-busting’ drug 2. Adverse effects in adults are well documented, but there are limited data on effects in children or adolescents 3 4.…”
Section: Introductionmentioning
confidence: 99%
“…Spontaneous reporting (SR) of adverse drug reactions (ADRs) is a critical activity for healthcare professionals, as ADRs are one of the leading causes of morbidity and mortality and a threat to public health . The identification of pharmacovigilance (PV) activities as common objectives in the global community triggered international collaborations to enhance patient safety .…”
Section: Introductionmentioning
confidence: 99%